Identification of drivers of Rift Valley fever after the 2013–14 outbreak in Senegal using serological data in small ruminants - Seck, Ismaila; Lo, Modou Moustapha; Fall, Assane Gueye; Diop, Mariane; Ciss, Mamadou; Cêtre-Sossah, Catherine Béatrice; Faye, Coumba; Lo, Mbargou; Gaye, Adji Mareme; Coste, Caroline; Squarzoni-Diaw, Cécile; Alambedji, Rianatou Bada; et al. (PLoS neglected tropical diseases, 2022)
Rift Valley fever (RVF) is a mosquito-borne disease mostly affecting wild and domestic ruminants. It is widespread in Africa, with spillovers in the Arab Peninsula and the southwestern Indian Ocean. Although RVF has been circulating in West Africa for more than 30 years, its epidemiology is still not clearly understood. In 2013, an RVF outbreak hit Senegal in new areas that weren’t ever affected before. To assess the extent of the spread of RVF virus, a national serological survey was implemented in young small ruminants (6–18 months old), between November 2014 and January 2015 (after the rainy season) in 139 villages. Additionally, the drivers of this spread were identified. For this purpose, we used a beta-binomial ( B B ) logistic regression model. An Integrated Nested Laplace Approximation (INLA) approach was used to fit the spatial model. Lower cumulative rainfall, and higher accessibility were both associated with a higher RVFV seroprevalence. The spatial patterns of fitted RVFV seroprevalence pointed densely populated areas of western Senegal as being at higher risk of RVFV infection in small ruminants than rural or southeastern areas. Thus, because slaughtering infected animals and processing their fresh meat is an important RVFV transmission route for humans, more human populations might have been exposed to RVFV during the 2013–2014 outbreak than in previous outbreaks in Senegal.